2022
DOI: 10.1111/acel.13580
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of myofibroblast phenotype in cellular senescence

Abstract: Cellular senescence is an antiproliferative response with a critical role in the control of cellular balance in diverse physiological and pathological settings. Here, we set to study the impact of senescence on the regulation of cell plasticity, focusing on the regulation of the myofibroblastic phenotype in primary fibroblasts. Myofibroblasts are contractile, highly fibrogenic cells with key roles in wound healing and fibrosis. Using cellular models of fibroblast senescence, we find a consistent loss of myofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…cells. In addition, we confirmed these results by analysing gene expression of wellstablished senescence markers: IL-1β, p21, IL-6 and IL-8 [62], observing a significant induction for all of them after MAPK11 knockdown compared to E.V. cells (Fig.…”
Section: Resultssupporting
confidence: 80%
“…cells. In addition, we confirmed these results by analysing gene expression of wellstablished senescence markers: IL-1β, p21, IL-6 and IL-8 [62], observing a significant induction for all of them after MAPK11 knockdown compared to E.V. cells (Fig.…”
Section: Resultssupporting
confidence: 80%
“…We observed that fibroblast markers were unchanged in primed cells (versus nonprimed cells), but primed cells did express comparatively lower levels of markers of fibroblast activation and myofibroblast differentiation. The hiF-T cell line is a secondary fibroblast line (meaning that it was formed from reprogramming fibroblasts into iPSCs and then differentiating a clone back into fibroblast-like cells), so it is unclear how to interpret the expression of these markers in this line, which may arise from the culturing conditions used (Baranyi et al, 2019; Baum & Duffy, 2011; Doolin et al, 2021; Hinz et al, 2012; López-Antona et al, 2022; Masur et al, 1996; Pakshir et al, 2020). The literature is also mixed on the effects of fibroblast activation on iPSC reprogramming, with some studies reporting that activated fibroblasts and myofibroblasts taken from fibrotic or damaged tissues are known to be more resistant to iPSC reprogramming (Song et al, 2016; Tanaka et al, 2020) while others reporting that mouse fibroblasts with an enhanced propensity to form myofibroblasts in uninduced populations reprogram into iPSCs with higher efficiency (Koumas et al, 2003; Nemajerova et al, 2012; Sanders et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on tissue context and cell type, senescence may also promote the myofibrogenic differentiation, such as in wounded skin (Demaria et al, 2014) or inhibit it through a modulation of Notch/ TGFβ axis (Lopez-Antona et al, 2022). Our data demonstrate that Notch activation has a major impact in the determination of AT progenitor fate since it impairs white and brite adipogenesis while promoting myofibrogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…Senescent AT stromal cells from aged/obese mice and humans exhibit a decreased adipogenic potential (Le Pelletier et al, 2021; Xu, Palmer, et al, 2015), while a targeted reduction in senescence enhances adipogenesis (Xu, Palmer, et al, 2015). Depending on tissue context and cell type, senescence may also promote the myofibrogenic differentiation, such as in wounded skin (Demaria et al, 2014) or inhibit it through a modulation of Notch/TGFβ axis (Lopez‐Antona et al, 2022). Our data demonstrate that Notch activation has a major impact in the determination of AT progenitor fate since it impairs white and brite adipogenesis while promoting myofibrogenesis.…”
Section: Discussionmentioning
confidence: 99%